Clinical and Microbiological Characteristics of Deep Neck Abscesses in Pediatrics: Analysis of a Case Series from a 3rd Level Pediatric Hospital - Marcello Mariani; Carolina Saffioti; Alessio Mesini; Candida Palmero; Roberto D'Agostino; Sabrina Garofolo; Andrea Rossi; Maria Beatrice Damasio; Elio Castagnola (MDPI AG, 2023)
As there is currently no consensus on managing deep neck infections in pediatric populations, we report a case series from a large pediatric hospital. Clinical data of patients discharged from Istituto Gaslini-Children's Hospital from January 2014 to June 2020 with peritonsillar, parapharyngeal, or retropharyngeal abscess diagnoses were collected. A total of 59 patients were identified. Patients underwent surgical drainage in 47% of cases. Streptococcus mitis/oralis was the most isolated pathogen. Surgically treated patients did have larger abscesses compared to others, but there were no differences in the duration of hospitalization. Children who received NSAIDs at home had significant delays in diagnosis (median 4 vs. 1.5 days, p = 0.008). In our experience, clinical presentation of DNIs is often evocative, but evaluation should include imaging with CT/MRI. Surgery is effective in larger abscesses, allowing for etiological diagnosis with consequent antibiotic adjusting. From an anamnestic point of view, home medications such as NSAIDs could delay diagnosis.